The emotionally intelligent child : effective strategies for parenting self-aware, cooperative, & well-balanced kids - Katz, Rachael; Hadani, Helen Shwe (New Harbinger Publications, Inc., 2022)
"Parents often wonder what's going on in their child's mind when they throw a temper tantrum, behave badly, or refuse to cooperate. Written by two experts in child development and psychology, The Emotionally Intelligent Child offers a groundbreaking approach for understanding children's behavior in the context of their development, as well as tips for parenting with patience, and actionable strategies for helping kids cultivate emotional intelligence-an essential character trait for succeeding in our highly social world"--